Applying psychophysiological coherence training based on HRV-biofeedback to enhance pilots’ resilience and wellbeing - Zhang, Jingyi; Li, Wen-Chin; Andrews, Gavin (Elsevier, 2022)
Introduction. The COVID-19 pandemic not only limited pilots’ proficiency in performing routine tasks, but also increased stress levels and operational risk due to new procedures in flight operations related to safety and health regulations. There is, therefore, an increasing need to improve pilots’ mental and physical health to maintain aviation safety Research question. (1) Does the practice of psychophysiological coherence using heart rate variability (HRV) biofeedback and the Quick Coherence Technique (QCT) improve pilots’ resilience? (2) What effects does psychophysiological coherence practice have on pilots’ resilience and wellbeing? Method. Eighteen commercial pilots’ perceived stress and wellness were evaluated subjectively by the Perceived Stress Scale (PSS) and Ardell Wellness Self-Assessment (AWSA). They were taught the QCT for facilitating psychophysiological coherence, and their HRV data reflecting automatic nervous system (ANS) activities were collected as they practiced QCT via Inner Balance HRV sensors. Results. The QCT training improved pilots’ AWSA scores (t = -3.55, p = .002) and decreased PSS scores (t = 6.37, p < .001). Pilots’ post-training HRV were improved with SDNNs higher than pre-training, t = -4.88, p < .001; normalized low frequency (LF) power increased (t = -10.91, p < .001) and low-frequency to high-frequency (LF/HF) ratios increased (t = -3.92, p = .001). Additionally, pilots’ post-training respiration rates were lower than pre-training, t = -2,45, p = .025. Discussion. Based on the empirical data analysis, HRV-biofeedback QCT can improve psychophysiological coherence and thereby increase pilots’ resilience and wellbeing. Increased post-training SDNNs, normalized LF power, and LF/HF ratio indicate the improvement of ANS control and balance, and stress management capacity. These findings demonstrate the effectiveness of HRV-biofeedback QCT training in improving psychophysiological coherence, which confers real-time and post-practice benefits of optimal energy utility and self-regulation in challenging situations on flight operations and everyday life. Conclusion. This research demonstrates significant benefits of a short session of HRV-biofeedback QCT on pilots’ resilience and cognitive process by improving psychophysiological coherence. HRV-biofeedback QCT training can be an effective intervention for aviation authorities and airline operators to develop peer support programs for pilots to increase psychological resilience and wellbeing. This may be particularly beneficial given the various challenges presented to pilots in their preparation for return to normal operations.
Keywords: Biofeedback Breathing; Heart Rate Variability; Quick Coherence Technique; Resilience